KANDUNGAN SENYAWA BIOAKTIF DAN KARAKTERISTIK SENSORIS EKSTRAK SIMPLISIA BUNGA KAMBOJA (PLUMERIA SP.) - WRASIATI, LUH PUTU; HARTATI, AMNA; YUARINI, DEWA AYU ANOM (Jurnal Biologi Udayana; Vol 15 No 2 (2011): Jurnal Biologi, 2011)
This research was carried out to identify the bioactive compounds and sensory characteristics of simplisia extract of frangipani. The kinds of frangipani used in this research were ”Local Bali” frangipani and ”Cendana” frangipani which belong to Plumeria alba, and pink frangipani and ”Sudamala” frangipani which are member of Plumeria rubra. The method used in this research was explorative method to find out the bioactive compounds such as tannin, total phenol, and vitamin C content. The study also observed the sensory characteristics such as flavour, aroma, and colour of simplisia extract of frangipani. The results indicated that the highest tannin content was found in simplisia extract of ”Cendana” frangipani (4.02%), and the lowest tannin content was found in local frangipani (2.32%). The highest total phenol content was found at simplisia extract of ”Sudamala” frangipani (18.94 mg GAE/g) and the lowest content was found at ”Local Bali” frangipani (15.11 mg GAE/g). The highest value of vitamin C was found in ”Cendana” frangipani (2.76 mg/100 g), and the lowest value was found at pink frangifani (1.89 mg/100 g). The panelist preference test indicated that the color of frangipani extract ranged from yellow and brown up to brownies red (color score ranged from 2.66 until 3.97). The score of frangipani extract aroma ranged from 3.58 until 4.07 with criteria of a little specific frangipani smelt until specific frangipani. While, the preference test for flavor indicated that the score of frangipani taste ranged from 3.51 until 4.12 with the criteria of rather astringent and a little sour to astringent.
Keywords: bioactive compounds; sensory characteristics; simplisia extract of frangipani